Serum interleukin-6 as a serologic marker of chronic periapical lesions: a case-control study - Shahrzad Nazari; Farzad Esmaeili; Mohammad Vahedi; Hamid Reza Abdolsamadi; Shermin Abdollahzadeh (Tabriz University of Medical Sciences, 2008)
Background and aims. Chronic periapical disease with pulpal origin is an inflammatory condition caused by bacterial infection. Chronic infection could affect general health by increasing the production of cytokines such as interleukin-6 (IL-6) that probably play a role in pathogenesis of pulpal and periapical diseases. The aim of the present study was a comparative evaluation of the level of serum IL 6 in patients with periapical lesions and healthy controls.
Materials and methods. This analytical case-control study included 40 patients with chronic periapical lesions and 40 individuals without any oral diseases. All of the participants were in good general health. After obtaining an informed consent, clinical and radiographic examinations were carried out and blood samples were collected. Serum IL-6 was measured using ELISA. Data were analyzed using t-test by SPSS 14.0 computer software.
Results. Serum IL-6 concentration was significantly higher in test group compared to the controls (P < 0.05).
Conclusion. The results of the present study indicate that IL-6 produced in periapical lesions may serve as a marker of pathologic inflammatory activities in chronic periapical lesions.